Antiviral activity and possible mechanism of action of constituents identified in Paeonia lactiflora root toward human rhinoviruses. - Luong Thi My Ngan; Myeong Jin Jang; Min Jung Kwon; Young Joon Ahn (PLoS ONE, 2015)
Human rhinoviruses (HRVs) are responsible for more than half of all cases of the common cold and cost billions of USD annually in medical visits and missed school and work. An assessment was made of the antiviral activities and mechanisms of action of paeonol (PA) and 1,2,3,4,6-penta-O-galloyl-β-D-glucopyranose (PGG) from Paeonia lactiflora root toward HRV-2 and HRV-4 in MRC5 cells using a tetrazolium method and real-time quantitative reverse transcription polymerase chain reaction and enzyme-linked immunosorbent assay. Results were compared with those of a reference control ribavirin. Based on 50% inhibitory concentration values, PGG was 13.4 and 18.0 times more active toward HRV-2 (17.89 μM) and HRV-4 (17.33 μM) in MRC5 cells, respectively, than ribavirin. The constituents had relatively high selective index values (3.3->8.5). The 100 μg/mL PA and 20 μg/mL PGG did not interact with the HRV-4 particles. These constituents inhibited HRV-4 infection only when they were added during the virus inoculation (0 h), the adsorption period of HRVs, but not after 1 h or later. Moreover, the RNA replication levels of HRVs were remarkably reduced in the MRC5 cultures treated with these constituents. These findings suggest that PGG and PA may block or reduce the entry of the viruses into the cells to protect the cells from the virus destruction and abate virus replication, which may play an important role in interfering with expressions of rhinovirus receptors (intercellular adhesion molecule-1 and low-density lipoprotein receptor), inflammatory cytokines (interleukin (IL)-6, IL-8, tumor necrosis factor, interferon beta, and IL-1β), and Toll-like receptor, which resulted in diminishing symptoms induced by HRV. Global efforts to reduce the level of synthetic drugs justify further studies on P. lactiflora root-derived materials as potential anti-HRV products or lead molecules for the prevention or treatment of HRV.